Rumi Concept of Love: The Path to Interfaith Harmony and Peace - Shadiqin, Sehat Ihsan; Wahyudi, M. Agus; Alfiatunnur, Alfiatunnur; Jamil, Shabrun (Al-Albab, 2024)
Building mutual understanding among people of different religions is crucial in anticipating issues arising from individual religious identities. The concept of love, as viewed by Jalaluddin Rumi, can serve as a medium for nurturing interfaith peace. Rumi believed that love is at the core of human existence and emphasized its power in achieving tranquility. Through Rumi’s teachings, we gain an understanding of the significance of compassionate love in fostering mutual understanding and respect among different faiths. This article delves into Rumi’s life and works, highlighting his contributions to Sufism and his unique perspective on love. Furthermore, it delves deeper into Rumi’s concept of love. The aim of this paper is to contribute to the field of interfaith studies by exploring the potential of Rumi’s concept of love to promote mutual understanding and respect among religions through poetry and Rumi’s teachings. The research employs a qualitative method, specifically a literature review, drawing data from various references, books, and articles related to Rumi’s works and thoughts, particularly those discussing the concept of love. The findings reveal that Rumi’s concept of love can serve as a medium for addressing religious conflicts and building a more peaceful world. By embracing Rumi’s teachings on love, we learn to see beyond our differences and connect with each other at a deeper level.